Transforming Fiqh Education for the Twenty-First Century: The Role of Problem-Based and Project-Based Learning - Asis Saefudin; Ika Berdiati (SCAD Independent, 2026)
This study examines how Problem-Based Learning (PBL) and Project-Based Learning (PjBL) contribute to the transformation of Fiqh Education in Islamic Higher Education. Although twenty-first-century competencies have become central to contemporary educational transformation, their integration into Islamic legal education remains relatively underexplored, particularly in relation to contextual and competency-oriented pedagogical practices. This study aims to analyze how PBL and PjBL foster the development of collaboration, communication, critical thinking, and creativity (4Cs) while reshaping the learning dynamics of Fiqh education. The study employed a mixed-methods approach using a Sequential Explanatory Design involving 38 students in the Primary Madrasah Teacher Education Program at UIN Sunan Gunung Djati Bandung. Data were collected through competency assessment rubrics, classroom observations, and in-depth interviews and analyzed using quantitative and qualitative techniques. The findings indicate that PBL and PjBL positively contributed to the development of students’ twenty-first-century competencies, particularly collaboration, communication, and creativity, while critical thinking developed more gradually. The study also reveals that these active pedagogical approaches transformed Fiqh learning from a predominantly normative and lecturer-centered model into a more dialogic, contextual, collaborative, and student-centered educational process. These findings contribute to the growing discourse on competency-oriented pedagogy and demonstrate that the transformation of Fiqh Education is both feasible and necessary for responding to contemporary educational demands without diminishing its intellectual and spiritual foundations.